A gamification framework to enhance students’ intrinsic motivation on MOOC - Rujianto Eko Saputro; Sazilah Salam; Mohd. Hafiz Zakaria; Toni Anwar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Technological development supports the distribution of education to various parts of the world through online education. One of the learning media that supports the distribution of learning is the Massive Open Online Course (MOOC). However, MOOC has a low number of students who complete the course. Therefore, this research proposes a "gamification framework" through studies and various approaches in the field of games, intrinsic motivation elements, social learning, and interactive learning environments to overcome the low motivation of students. The proposed framework has been evaluated through validation by experts. The results found that the framework fulfilled the rules and suitability of the instruments and game elements used to increase the intrinsic motivation of students in online learning. Although there are some changes in the function and type of game elements used. For further research, the framework will be used as a guideline to build the Gamified MOOC Platform.